On the Facility, Felicity, and Morality of Measuring Social Change. - Churchman, C. West (The Accounting Review, 1971)
Abstract In a recent unpublished paper entitled Questions of Metric, Stafford Beer cites some letters to the newspaper, London Times, addressed to a question of social change. The issue concerned the seven hundred years old Norman Church of St. Michael of Stewkley, which stands square in the middle of a possible runway of a possible Third London Airport, not by design surely. A cost benefit analysis had been made by a commission for each alternative site of the proposed airport. It is really astonishing how many crisis-numbers are being thrown at the public these days. They all describe what programmers call the rate of activity in a certain sector of society. Since often the rate of activity, pollution or poverty or information, spread yields uneasy or horrible feelings, people and politicians are apt to conclude that something must be done to lessen the rate, or even to make it negative. But even if the disinterested observer is telling us about real impending disaster provided an activity continues to increase, it by no means follows that he is telling us about real social change in a pragmatic sense.